The Effectiveness of Soaking the Feet in Salt Water to Reduce the Degree of Edema in Pregnant Women Trimester III - Arlinda Patola; Feva Tridiyawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims : Non-pharmacological management of foot edema in pregnant women is using foot soak therapy in salt warm water mixed with. This study aimed to determined the effect of soaking the feet in salt water to reduce the degree of edema among trimester III pregnant woman. Design : This research method used pre-experimental design with one group pretest - posttest design. Data collection was carried out using primary data, namely data obtained from observations. The data collection instrument used was an observation sheet Methdos : The sample in this study were all pregnant women in the third trimester who experienced edema as many as 20 people, the sampling technique was purposive sampling. Results : There was a decrease in the degree of edema before and after soaking the feet in salt water, from the third degree of edema to the second degree of edema (p value 0.000). Conclusions : There is an effectiveness of soaking the feet in salt water to reduce the degree of edema in third trimester pregnant women. It is expected that health workers will provide nursing care to reduce edema non-pharmacologically.